“Las destrezas cognitivas en el proceso de la estimulación temprana en los niños y niñas del centro de educación inicial infantil "Alfonso Chávez Jara", de la ciudad de Riobamba, provincia de Chimborazo periodo 2015-2016" - Cruz Espinoza, Adriana Rocío (2017)
The present investigation is constituted by chapters. Chapter I corresponds to the frame of reference, which contains the formulation and approach of the problem, the objectives, both general and specific, as well as the justification of research and the importance of research. In chapter II is the theoretical framework, this chapter covers topics and sub topics such as: cognitive skills, early stimulation in children, education, etc. Based on data provided by the Early Childhood Education Center "Alfonso Chávez Jara", in addition to books by renowned authors dealing with each of the subjects investigated. Chapter III is the methodological framework, this unit covers methods, techniques to be followed for the proper management of the information obtained, and for the determination of the sample. Chapter IV sets out the conclusions and recommendations, in this chapter, the conclusions and recommendations reached by the theme of child labor in the city of Riobamba. Chapter V, this research is presented a teaching guide that helps the development of cognitive skills through early stimulation in children, the Center for Early Childhood Education Alfonso Chavez Jara.